Turkish Multinationals Market Entry and Post-Acquisition Strategy - Ayden, Yuksel (Palgrave Studies of Internationalization in Emerging Markets,, 2018)
This book explores the internationalization of Turkish multinationals by examining a set of firms from various industries and providing eleven detailed case studies. The authors aim to discover the reasons behind the drive for internationalization within the firms, and how their internationalization processes work. By focusing on a medium-sized emerging country, which is strategically located at the intersection of European, Asian and African markets, Turkish Multinationals provide a significant contribution to research on multinational firms in emerging countries. Topics discussed include: strategic motives for and drivers of internationalization at multiple levels (firm, industry and institutional); the location, ownership and entry modes of multinational firms; and their market entry and post-acquisition strategies, which are critical to the evolution of the internationalization process. This innovative book will offer an alternative perspective to current debate on emerging markets, and will be of great interest to both academics of global strategy and international business, and policy-makers.